2016
DOI: 10.12693/aphyspola.130.107
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Risk Factors Impact on the Construction Projects Implementation Using Fuzzy Sets Theory

Abstract: The complexity of construction projects increases the likelihood of hazards affecting their successful implementation. There are many risk factors that lead to the failure of the project. These factors should be identified and ordered both because of their degree of importance (significance) and level (volume) of a given factors. This is very important in order to determine their effect on the construction project. Typically, the threats for the construction project include the extension of the project duratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 7 publications
0
18
0
Order By: Relevance
“…There are different techniques in the literature that benefit from fuzzy set theory. One of the important elements of the fuzzy set theory is a linguistic variable which adopts natural language expressions as its value [32]. In this study performance criteria are sorted in descending order in an attempt to make strategic decisions.…”
Section: Methodsmentioning
confidence: 99%
“…There are different techniques in the literature that benefit from fuzzy set theory. One of the important elements of the fuzzy set theory is a linguistic variable which adopts natural language expressions as its value [32]. In this study performance criteria are sorted in descending order in an attempt to make strategic decisions.…”
Section: Methodsmentioning
confidence: 99%
“…Methodology proposes a whole range of tools: documentation reviews, information gathering techniques (brainstorming, Delphi technique, interviewing, root cause analysis), checklist analysis, assumptions analysis, diagramming techniques (cause and effect diagrams, system of process flow charts, influence diagrams), SWOT analysis and expert judgement. As a result of the tools are the following products: list of identified risks, list of potential responses, root causes of risks, updated risk categories [11,15,16].…”
Section: Identifying Risksmentioning
confidence: 99%
“…a i -the value of type a of input set, from i set of input data after standardization, a 01 -the value of type of input observed in process (before standardization), i -consecutive number of the process being observed. Multi-Layer Perceptron (MLP) type of ANN was used, as it was found that MLP networks have higher abilities to generalize input-output relations than ANN of Radial Basis Function (RBF) [5,6]. It was checked empirically that for this case, i.e.…”
Section: Ann Trained With the Set Of Real Numbers As An Output Reprementioning
confidence: 99%